Minding the world: Adorno’s critique of idealism - Hammer, Espen (Philosophy & social criticism, 2000)
Against Jürgen Habermas’ view that Adorno’s thinking is characterized by a commitment to a philosophy of consciousness, and that therefore the only alternative to identitarian reason is to appeal to an intuitive competence operating beyond the range of conceptual thought, it is arged (1) that Adorno conceptualizes the modern epistemic subject (the subject of a philosophy of consciousness) as based on a reification, and (2) that he denies the possibility of a concept-transcendent (foundationalist) constraint on judgments. In seeking to demonstrate against versions of subjective idealism and foundationalism how thought can be responsive to a non-identical (mind-independent) reality, Adorno defends an intersubjectivist and historicist view of knowledge according to which the operative and yet anamnetic aspiration of knowledge is to know reflectively the object as it is in itself. The conclusion is that although Adorno questions the modern (Kantian) stress on epistemic autonomy, he does not take leave of modernity in the sense ascribed to him by Habermas.